Guiding the Selection of Processing Additives for Increasing the Efficiency of Bulk Heterojunction Polymeric Solar Cells. Issue 3 (23rd September 2013) - Vongsaysy, Uyxing; Pavageau, Bertrand; Wantz, Guillaume; Bassani, Dario M.; Servant, Laurent; Aziz, Hany
<x xml:space="preserve">Abstract</x> In bulk heterojunction (BHJ) polymeric organic solar cells (OSCs), the use of processing additives in the material formulation has emerged as a promising, cost‐effective, and widely applicable method for optimizing the phase separation between the donor (D) and acceptor (A) materials, thus increasing their efficiency. So far, however, there has been no systematic approach for identifying suitable processing additives for a given D:A system. A method based on the Hansen solubility parameters (HSPs) is proposed for guiding the selection of processing additives for a given D:A combination. The method is applied to the archetypical poly(3‐hexylthiophene) (P3HT) and [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) system. The HSPs of these materials are determined and used to define a set of numerical criteria that need to be satisfied by a processing additive in order for it to be effective in realizing a higher efficiency OSC. Applying the selection criteria results in the identification of three novel processing additives. OSCs made of these formulations demonstrate an increase in their short‐circuit current density (JSC) and power conversion efficiency (PCE). These results demonstrate the efficiency of these novel processing additives and show that the HSPs represent a useful tool to determine and explore new types of processing additives for BHJ‐OSCs.